Abolition for the people : the movement for a future without policing & prisons - Kaepernick, Colin, 1987-; Davis, Angela Y. (Angela Yvonne), 1944-; Browne, Simone, 1973-; Neal, Mark Anthony; Laymon, Kiese; Nopper, Tamara K.; Schrader, Stuart, 1978-; Lewis, Talila A.; Meiners, Erica R.; Nopper, Tamara K.; Ross, Kihana Miraya; Crenshaw, Kimberlé; et al. (Kaepernick Publishing, 2021)
The former NFL star turned social activist presents 30 essays from political prisoners, grassroots organizers and scholars such as Angela Davis and Dereck Purnell that focus on the police and incarceration abolition movement.